Growth of Zinc Oxide Nanorods with the Thickness of Less than or Equal to 1 μm through Zinc Acetate or Zinc Nitrate for Perovskite Solar Cell Applications - Albertus Bramantyo; Kenji Murakami; Masayuki Okuya; Arief Udhiarto; Nji Raden Poespawati (Journal of Engineering)
Arrays of zinc oxide (ZnO) nanorod (NR) were fabricated in a vertical axis direction through the two-step method of seed layer’s deposition and growth of the NR. The seed layer was applied by spin coating with a three-time repetition (n) and rotational speed (v) at 3000 rpm. After the seed layer had grown, ZnO NRs were grown with a growth solution made by combining one zinc source with one hydroxide source. There were two different zinc sources, i.e., zinc acetate dehydrate and zinc nitrate hexahydrate and, for comparison, zinc acetate (ZA) and zinc nitrate (ZN) were each combined with the same hydroxide source, hexamethylenetetramine (HMT). Later, the growth solutions were processed by the chemical bath deposition (CBD) method using a waterbath machine. The CBD method was started at room temperature until it reached the designated temperature at 85°C. At that point, the growth time was calculated from the zero-minute condition. It was found that ZnO NRs had already grown at a thickness of about 100 nm for both ZA and ZN sources. The growth time varied at 15, 60, 90, and 120 minutes after the zero-minute point. By using two separate and independent zinc sources while growing ZnO NRs at various growth periods, several ZnO NRs’ thicknesses were controlled. According to a paper by Lee et al., the lower thickness of ZnO NRs boosted the charge transfer properties of perovskite solar cells (PSCs) because the series resistance between ZnO/perovskite interfaces was lessened. Scanning electron microscopy (SEM) images were observed to analyze the morphological shape of the ZnO NRs. X-ray diffraction (XRD) profiles were characterized to obtain the data for ZnO NR crystallinity. Full width at half maximum (FWHM) analysis was performed at the (002) ZnO peak to calculate the crystal size of the peak. From the results, the smallest crystallite sizes for ZnO NRs grown from ZA and ZN sources were 10.70 nm and 19.29 nm, respectively, which would be the most suitable condition for PSC application.